2015
DOI: 10.1063/1.4917531
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous C-V response correlated to relaxation processes in TiO2 thin film based-metal-insulator-metal capacitor: Effect of titanium and oxygen defects

Abstract: Capacitance-voltage (C V) and capacitance-frequency (C f) measurements are performed on atomic layer deposited TiO 2 thin films with top and bottom Au and Pt electrodes, respectively, over a large temperature and frequency range. A sharp capacitance peak/discontinuity (C V anomalous) is observed in the C V characteristics at various temperatures and voltages. It is demonstrated that this phenomenon is directly associated with oxygen vacancies. The C V peak irreversibility and dissymmetry at the reversal dc vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…For the 0.005 mbar sample, κ shows a decrease of 70% going through the relaxation, reaching a value at 100 kHz of around 31. This latter value corresponds well to what is observed in other amorphous thin films [14]. The high κ observed in the samples grown at low oxygen pressure would therefore be generated directly by the accumulation of the mobile charges at the dielectric/electrode interface.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…For the 0.005 mbar sample, κ shows a decrease of 70% going through the relaxation, reaching a value at 100 kHz of around 31. This latter value corresponds well to what is observed in other amorphous thin films [14]. The high κ observed in the samples grown at low oxygen pressure would therefore be generated directly by the accumulation of the mobile charges at the dielectric/electrode interface.…”
Section: Resultssupporting
confidence: 88%
“…TiO 2 is a versatile material, useful for a large range of applications such as dye-sensitized solar cells [1,2], photocatalysis [3], resistive switching [4][5][6], field emission [7] and as transparent conductor [8] or diluted magnetic semiconductors if doped [9,10]. Notably, TiO 2 is also part of the so-called highk dielectrics, showing a strongly growth dependent dielectric constant of ≈80 [11], and was used therefore as a dielectric in capacitors [12][13][14] or as gate oxide in MOSFETs [15,16]. This high versatility of TiO 2 for application is primarily a consequence of the wide range of electronic properties which can be encountered in TiO 2 , ranging from an insulating character to a high mobility semi-conductor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that a pure TiO 2 dielectric can reach such high values of κ in the rutile crystalline state, , but this phase is hard to access and the dielectric losses and leakage current are typically higher. Amorphous TiO 2 exhibits a κ of 20–40, , but the leakage current is still enhanced compared to the subnanometric laminates presented here. The leakage current of pure TiO 2 was shown to decrease with lamination of Al 2 O 3 , but so does κ. , Most of the values found for crystalline nanometric laminates are ranging from 10 to 40, ,, in the amorphous phase κ = 8 .…”
Section: Discussionmentioning
confidence: 67%
“…x [598]; [523,[598][599][600][601][602][603]; [604,605]; [576,606]; b Ti(OEt) 4 [37,54,63,91,[607][608][609][610][611][612][613][614][615][616][617]; [54,63,91] Note that a process (free from conventional oxygen sources) by combining TiCl 4 and Ti(O i Pr) 4 has also been demonstrated [798]. Note that in references [792][793][794][795][796][797] a process with molecular N 2 O has also been reported.…”
Section: Precursors and Processesmentioning
confidence: 96%